Hidden emotions under the skin: autonomic reactivity on attentional regulation in insecure attachment - Silva, C. (2015)
The present study examined physiological reactivity to emotional stimuli as a function of attachment style. Skin conductance responses (SCRs) and heart rate (HR) changes were simultaneously recorded while participants engaged in a visual attentional task. The task included positive, neutral, and negative emotional pictures, and required the identification of a target (neutral picture rotated 90° to the left or right), among a stream of pictures in which an emotional distracter (positive or negative) was presented. Participants additionally rated each of the emotional distracters for valence and arousal. Behavioral results on the attentional task showed that positive pictures facilitated overall target detection for all participants, compared to negative and neutral pictures, and that anxiously attached participants had significantly lower accuracy scores, relative to the other groups. Affective ratings indicated that positive pictures were rated as being more pleasant than negative ones, although no differences were found in HR changes to picture valence. In contrast, negative pictures were evaluated as being highly arousing. Consistent with this, negative pictures elicited larger SCRs in both insecure anxious and avoidant groups, especially for the anxious while the secure group showed SCRs unaffected by stimuli’s arousal. Present results show that individuals with different attachment styles reveal distinct patterns of attentional bias, appraisal, and physiological reactivity toward emotionally arousing stimuli. These findings further highlight the regulatory function of the attachment system.